Emerging of Heterostructure Materials in Energy Storage: A Review - Li, Yu; Zhang, Jiawei; Chen, Qingguo; Xia, Xinhui; Chen, Minghua (Advanced materials (Weinheim), 2021)
With the ever‐increasing adaption of large‐scale energy storage systems and electric devices, the energy storage capability of batteries and supercapacitors has faced increased demand and challenges. The electrodes of these devices have experienced radical change with the introduction of nano‐scale materials. As new generation materials, heterostructure materials have attracted increasing attention due to their unique interfaces, robust architectures, and synergistic effects, and thus, the ability to enhance the energy/power outputs as well as the lifespan of batteries. In this review, the recent progress in heterostructure from energy storage fields is summarized. Specifically, the fundamental natures of heterostructures, including charge redistribution, built‐in electric field, and associated energy storage mechanisms, are summarized and discussed in detail. Furthermore, various synthesis routes for heterostructures in energy storage fields are roundly reviewed, and their advantages and drawbacks are analyzed. The superiorities and current achievements of heterostructure materials in lithium‐ion batteries (LIBs), sodium‐ion batteries (SIBs), lithium‐sulfur batteries (Li‐S batteries), supercapacitors, and other energy storage devices are discussed. Finally, the authors conclude with the current challenges and perspectives of the heterostructure materials for the fields of energy storage. Constructing heterostructures is an effective way to enhance the electrochemical performance of active materials due to the unique heterointerface structure and some unrevealed synergistic effects. An overview of the recent advancements in heterostructured materials in terms of enhanced mechanism, synthesis techniques, and electrochemical performance is provided. Future development trends for design of heterostructured electrodes are analyzed.